Edukasi Perawatan Paliatif Bagi Tenaga Kesehatan di Panti Werdha Non Mandiri Melania Pademangan Jakarta Utara - Kristoforus Marselinus; Yurita Mailintina; Ribka Sabarina Panjaitan; Ika Mustafida; Ria Efkelin Mose; Imelda Imelda; Lipin Lipin (Jurnal Kemitraan Masyarakat, 2024)
Palliative care is a treatment approach that aims to improve the quality of life of patients facing serious illnesses, especially when the disease is no longer responsive to curative treatment. Palliative care not only focuses on controlling physical symptoms, but also provides psychological, social, and spiritual support to patients and their families. With this education, health workers are expected to: Increase Knowledge and Skills: Education will increase the knowledge of health workers about pain management, chronic symptom management, and psychosocial and spiritual support for home residents. From the data displayed in the table, it can be concluded that from 30 respondents obtained an N-Gain Score of 64.3, indicating that the method applied by the researcher in this activity is quite effective. In addition, the distribution of N-Gain Score with a value of 0.6 indicates that the strength or category in this study is at a moderate level, the results of the pre-test and post-test that have been carried out by the researcher have increased significantly, which is 50%.